(untitled) (Global Journal of Science Frontier Research, 2023)
The field study was laid out during three consecutive years of 2005-06 to 2007-08 at Mainpuri, Farrukhabad and Kannauj districts. The operational area located between catchments area of Ganga and Kali rivers. The experimental soils were loamy sand, sandy loam and light loam in texture. The analysis of composite soil sample displayed low status of plant nutrients. The four treatments i.e, guava + groundnut cv. Dh-86 + soil application of neem leaves power @ 50 kg/ha and spraying of neem oil on guava plants @ 2.5 lit/ha, guava + groundnut cv. Dh-86 + soil application of neem leaves powder @ 100 kg/ha and spraying of neem oil on guava plants @ 2.5 lit/ha, guava + groundnut cv ICGV 93468 + soil application of neem leaves powder @ 50 kg/ha and spraying of neem oil on guava plants @ 2.5 lit/ha and guava + groundnut cv. ICGV-93468 + soil application of neem leaves powder @ 100 kg/ha and spraying of neem oil on guava plants @ 2.5 lit/ha were tested. The farmers were suggested for plantation of guava at the spacing of 6×6 m 2 . The cultivars Dh-86 and ICGV-93468 (Avtar) were selected and planted between 5-10 March of experimental years. The 20 rows of groundnut were planted between two rows guava. The sowing of groundnut was made at spacing of 25 cm in rows.